2011
DOI: 10.2135/cropsci2010.08.0503
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ring‐Shaped Chalkiness and Osmotic Adjustment when Growing Rice Grains under Foehn‐Induced Dry Wind Condition

Abstract: Foehn-induced dry wind during grain filling increased ring-shaped chalky kernels in rice {Oryza sativa L.) plants. The objective of this study was to determine physiological mechanisms of the occurrence of ring-shaped chalky kernels. Rice plants were subjected to water deficit in a paddy field after shade by applying dry high-speed wind. Additionally, a growth chamber experiment was conducted with plants in pots to measure the water status under the dry wind condition for 24 h by combining in situ turgor {^'^)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 46 publications
9
40
0
Order By: Relevance
“…During the osmotic adjustment, turgor pressure can be maintained by accumulating osmotically active solutes, such as sugars and amino acids, into the cells (Morgan, 1977; Meyer and Boyer, 1981). As reported previously (Wada et al, 2011; Wada et al, 2014), osmotic adjustment also occurred in the rice endosperms cells growing under dry wind conditions prior to chalky ring formation. On-site cell metabolomics and in situ turgor assay conducted in outer endosperms indicated clear treatment differences in the heat adaptive responses (Figure 3B-E).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…During the osmotic adjustment, turgor pressure can be maintained by accumulating osmotically active solutes, such as sugars and amino acids, into the cells (Morgan, 1977; Meyer and Boyer, 1981). As reported previously (Wada et al, 2011; Wada et al, 2014), osmotic adjustment also occurred in the rice endosperms cells growing under dry wind conditions prior to chalky ring formation. On-site cell metabolomics and in situ turgor assay conducted in outer endosperms indicated clear treatment differences in the heat adaptive responses (Figure 3B-E).…”
Section: Discussionsupporting
confidence: 85%
“…Oryza sativa L. ‘Koshihikari’ potted plants were grown without giving a top dressing in Kyushu Okinawa Agricultural Research Center, Chikugo, Japan, according to the method of Wada et al (2011). At flowering, the potted plants grown in field were transferred to the walk-in environmentally-controlled growth chamber (26/22°C, 70/80% relative humidity, and 750 μmol photons m −2 s −1 photosynthetically active radiation [PAR]) set at the plant canopy using light emitting plasma (LEP) lamps (STA 41-02, Stray Light Optical Technologies, Inc., IN, the US) with a photoperiod of 13 h day/11 h night.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the inner endosperm cells, where a high frequency of chalky ring was observed, maintained endosperm cell turgor by osmotic adjustment under shortterm dry wind conditions prior to the chalky formation, which sustains the kernel development (Wada et al, 2011). And, a temporal reduction in starch biosynthesis with no starch degradation also occurred at osmotic adjustment during short-term dry wind conditions (Wada et al, 2014).…”
Section: Chalky Grain Induced By Hot and Dry Windmechanisms And Countmentioning
confidence: 99%
“…Also, it has been widely recognized that foehn (dry high-speed wind) causes an excessive cuticular transpiration from the panicle that subjects the plants to the short-term shoot water deficit, resulting in spikelet sterility (Ishihara et al, 1990;Muramatsu, 1982;O'Toole et al, 1984). Aside from the spikelet sterility at flowering, dry wind occurred during the ripening substantially increases ring-shaped chalky kernels, called milky-white rice, and contrastingly lowers perfect rice (Ishihara et al, 2005;Wada et al, 2011). It is also known that rice plants during the middle ripening stage are particularly vulnerable to wind-induced water deficit, compared with other ripening stages (Oya & Yoshida, 2008).…”
Section: Chalky Grain Induced By Hot and Dry Windmechanisms And Countmentioning
confidence: 99%
See 1 more Smart Citation